Experimental and numerical studies on vibration characteristics of laminated composite skewed shells with cutout. (15th March 2019) - Mandal, Arpita; Ray, Chaitali; Haldar, Salil
Abstract: The findings of the experimental and numerical investigations on vibration characteristics of laminated skewed shells with cutout are presented in this paper. The shell laminates have been fabricated in the laboratory by adopting resin infusion technique. Experimental analysis is conducted using Photon plus data acquisition system along with accelerometer and impact hammer to identify the influence of skew angle and cutout on the natural frequencies of laminated shell. The results obtained in the present investigation indicate that cutout and skew angle bear remarkable influencing factor to control the frequencies of laminated skewed shells. Additional results obtained from extensive parametric study on various shells with cutout are presented which may be helpful for future researchers.